The Effect of Service Quality on Visitor Satisfaction of the Turkish University Fair 2025 Event by PT Trans Kreasindo Production Medan - Hidayat, Wahyu; Musriza, Irwan (Journal of Economics and Social Sciences (JESS), 2025)
The Turkish University Fair 2025 event is an activity carried out by PT Trans Kreasindo Proudction which was held at the Adimulya Hotel Medan. This activity was attended by students of the leading schools of the city of Medan. which amounted to 900 visitors. This research is categorized as quantitative descriptive research, where the research instruments are in the form of questionnaires, and literature studies. The population in this study is the Turkish Universities Fair 2025 event of 900 people. Sampling of 100 respondents used the slovin formula. The validity test tool used SPSS 25, the reliability test using Croanbach's Alpha formula and multiple linear regression analysis were used as hypothesis tests for this study. The results of this study show that the quality of service consisting of physical evidence (X1), reliability (X2), responsiveness (X3), assurance (X4) and empathy (X5), simultaneously (Test F) has a positive effect on visitor satisfaction. This indicates that of all the factors of physical evidence, reliability, responsiveness, assurance and empathy were able to influence visitor satisfaction by 78.6% and the remaining 21.4% can be explained by factors not studied in this study. In addition, the t-test partially the most dominant variable, namely Reliability (X2 = 0.661), became the most dominant factor influencing Visitor Satisfaction, followed by Responsiveness (X3 = 0.550), Physical Evidence (X1 = 0.477), and Assurance and Empathy (X4 and X5 = 0.464).